KAJIAN TENTANG PENAMBAHAN LATEKS KKK-60 DENGAN CAMPURAN ASPAL KONVENSIONAL - Sambodo, Sambodo; Rulhendri, Rulhendri (Universitas Ibn Khaldun Bogor, 2014)
This study uses a pen Asphalt 60/70 production Pertamina Cilacap, natural rubber (Latex KKK-60) production in the country that have been tested by the Center for Estate Crops Research Bogor, coarse and fine aggregate Ex stone-breaking machine (Stone Chrusher). Laboratory test results showed that the quality of the asphalt rubber (Latex KKK-60) of 3%, better quality when compared to petroleum asphalt mixture without Latex, because it can reduce the value of the penetration and softening point of asphalt marked increase with the increase of stability when tested with Marshall test equipment. Use of rubberized asphalt for road construction materials is an alternative that produces quality asphalt mixture with a better quality of asphalt mixture using petroleum asphalt without latex (conventional), and potential. Asphalt mixture with the addition of (Latex KKK-60) of 2% - 3% can increase the stability of 13.633% with the use of specifications HRS 30% coarse aggregate.